Impact of risk disclosures on IPO performance: Evidence from India - Khushboo Gupta; T. V. Raman; O. S. Deol; Kanishka Gupta (Финансы: теория и практика, 2021)
The main aim of the paper is to explore the performance of Indian IPOs in the context of risk disclosures in the offer documents. For the purpose of assessing the impact of risk disclosure factors on initial returns, subsequent returns and post issue risk of IPOs, the study has implemented ordinary least square regression. The study has analysed 109 IPOs that were listed in two main Indian stock exchanges (BSE and NSE) from 2015–2019. Outcomes of the present study are contrary to the previous studies which showed that information disclosure reduces the asymmetry, which is touted as the main reason for underpricing, the present study did not find any association between risk disclosures and underpricing. Quantitative risk measures showed positive association with 1-year returns, but qualitative measures failed to show any association. The post issue risk of the firms showed positive association with external risk factors listed in prospectus and negative association with liquidity. The results of this study are useful for the investors as based on the results they can make decisions about investing in Indian IPOs. Besides, the managers of issuing companies and lead managers of issues can use the results of this study to improve the pricing of issues. To the best of the authors’ knowledge no study has been done before in the Indian context which is specific to risk disclosures (quantitative and qualitative measures) and IPO performance. The present study seeks to fill this gap and contribute to the existing literature.